Help with boolean simplification

Thread Starter

exothesis

Joined Aug 31, 2010
3
Simplify XY'Z + X'Y'Z + XYZ

So far I have got:
Y'Z(X + X') + XYZ
--> Y'Z + XYZ

What do I do next? Any help would be appreciated.
 

Thread Starter

exothesis

Joined Aug 31, 2010
3
Never mind, I managed to solve the problem

--> XY'Z + X'Y'Z + XYZ
--> Y'Z(X + X') + XYZ
--> Y'Z(1) + XYZ
--> Y'Z + XYZ
--> Z(Y' + XY)
--> Z((Y' + X)(Y' + Y))
--> Z((Y' + X)(1))
--> Z(Y' + X)
--> Y'Z + XZ
 

Georacer

Joined Nov 25, 2009
5,182
I don't argue about how (Y' + X)(Y' + Y) becomes (Y' + X).
What troubles me is how (Y' + XY) becomes (Y' + X)(Y' + Y)
 

AMIT_GOHEL

Joined Jul 13, 2010
67
I don't argue about how (Y' + X)(Y' + Y) becomes (Y' + X).
What troubles me is how (Y' + XY) becomes (Y' + X)(Y' + Y)
Hello Georacer,

You may have confusion between math's we everyday use nd the boolean maths..

What you have asked is Distributive low of Boolean algibra.

Regards...
 

Georacer

Joined Nov 25, 2009
5,182
You are correct indeed! It's been a while since I read my Boolean Algebra manual (Morris Mano). It seems in Boolean logic the * operation (and) is distributive for the + (or) operation
i.e. \( x \cdot (y + z)= x \cdot y + x \cdot z \)

but also the + operation is distributive for the * operation
i.e. \( x+(y \cdot z)=(x+y)\cdot (x+z)\)

There's todays minimum positive knowledge for me!
 
Top